PHYSIOTHERAPY MANAGEMENT OF PATIENTS WITH DECUBITUS ULCERS IN THE SACRUM AND GLUTEAL REGION FOLLOWING RIGHT FEMORAL NECK FRACTURE SURGERY: A CASE REPORT - Nafisa Putri; Arin Supriyadi; Galih Adhi Isak Setiawan (CV. Fahr Publishing, 2026)
This case report aimed to describe physiotherapy management and clinical changes in a patient with pressure ulcer following postoperative right femoral neck fracture. A 60-year-old female after open reduction internal fixation presented with sacral and bilateral gluteal pressure ulcers, type 2 diabetes mellitus, severe anemia, systemic infection, and massive melena. Physiotherapy interventions included positioning, repositioning, breathing exercise, passive and active range of motion exercise, sensory stimulation, gradual mobility training, and family education. Clinical outcomes were evaluated descriptively across three sessions using the Behavioral Pain Scale, pressure ulcer observation, range of motion, manual muscle testing, and Functional Status Score for the Intensive Care Unit. During the intervention period, the Behavioral Pain Scale increased from 8 to 9, and pressure ulcer size remained unchanged. Passive range of motion was maintained from T1 to T3; however, muscle strength decreased from 3/5 to 2/5, and functional status declined from 2 to 0. These findings indicate that physiotherapy in this medically complex case primarily supported joint mobility maintenance, comfort, and prevention of further complications rather than functional recovery. Because this study involved a single patient with a short observation period, the findings should be interpreted descriptively and not as evidence of intervention effectiveness.